325PAssociation between immune-related adverse events and efficacy of immune checkpoint inhibitors in patients with advanced hepatocellular carcinoma. (24th November 2019) - Wong, L; Ang, A; Ng, K; Tan, S H; Choo, S P; Tai, D; Lee, J
Abstract: Background: More patients are receiving immune checkpoint inhibitors (ICI) for advanced hepatocellular carcinoma (HCC). We aim to explore whether an association exists between the presence of irAE and the efficacy of ICI in advanced HCC. Methods: We conducted a retrospective review of patients with advanced HCC who received ICIs between May 2015 - Nov 2018 at our centre. IrAE were graded according to the Common Terminology Criteria for Adverse Events v4.0. Response to ICI was evaluated based on RECIST v1.1 criteria. Results: Of the 114 patients studied, median age was 67.3yrs (23.5-84.9) and 78 (89.7%) were male. 68.4% experienced irAE of any grade (n = 78), with 21.8% being grade 3-4 (n = 17). None were grade 5. Patients in the any-irAE group had comparable ORR and significantly higher DCR than the no-irAE group (23.4 vs 10.0%, p = 0.118 and 64.9 vs 30.0%, p = 0.001). Median PFS and OS in the any-irAE group were significantly longer than the no-irAE group (4.0 vs 1.4mths, p < 0.001 and 16.4 vs 3.3mths, p < 0.001, respectively). Comparing against the no-irAE group, the G1/2-irAE and G3/4-irAE groups had significantly longer median PFS (G1/2 (3.7mths) vs no irAE (1.4mths), p < 0.001; G3/4 (11.6mths) vs. no irAE (1.4mths), p = 0.001) and OS (G1/2 (14.5mths) vs no irAE (3.3mths), p < 0.001; G3/4 (20.9mths) vs. no irAE (3.3mths), p < 0.001). Multivariate analysis showed that the presence of irAE was associated with longer median PFS [HR: 0.52 (95% CI 0.31-0.90), p = 0.018] and OS [HR: 0.38 (95% CI 0.20-0.71), p = 0.003]. Conclusions: The presence of irAE in advanced HCC patients treated with ICI could possibly predict better response and survival outcomes. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: S.P. Choo: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self): Bristol-Myers Squibb; Advisory / Consultancy, Research grant / Funding (self): Sirtex Medical; Advisory / Consultancy, Speaker Bureau / Expert testimony: Lily; Advisory / Consultancy: Novartis; Advisory / Consultancy: Eisai; Advisory / Consultancy: Bayer; Advisory / Consultancy: Celgene; Advisory / Consultancy: Ipsen. D. Tai: Research grant / Funding (self): Bristol-Myers Squibb; Advisory / Consultancy: Merck Sharp & Dohme; Advisory / Consultancy: Eisai; Honoraria (self), Advisory / Consultancy: Bayer; Advisory / Consultancy: Ipsen; Research grant / Funding (self): Sirtex. J. Lee: Advisory / Consultancy: Ipsen; Research grant / Funding (self): Bayer. All other authors have declared no conflicts of interest.